Vocational Teachers Readiness in Integration The Principles of Industrial Revolution 4.0 into The Learning Process - Muhammad Amin; Bima Mustaqim (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
The Indonesian government has started to fix the problem of industrial change with 'Making Indonesia 4.0' as a strategy to pave the way for Indonesia to become one of the new powers in Asia. One of the steps taken is to change the education system in Vocational High Schools in Indonesia where the education system has turned into competency-based and student-oriented education since April 2018. Teachers must be highly qualified in order to produce students capable of meeting the challenges of the industry revolution 4.0. In this article, we ask the following: